A bioconjugated MoS2 based nanoplatform with increased binding efficiency to cancer cells. (17th February 2020) - Kálosi, Anna; Labudová, Martina; Annušová, Adriana; Benkovičová, Monika; Bodík, Michal; Kollár, Jozef; Kotlár, Mário; Kasak, Peter; Jergel, Matej; Pastoreková, Silvia; Siffalovic, Peter; Majkova, Eva
Abstract : Preparation and study of a MoS2 nanosheet based nanoplatform for a cancer detection and treatment system equipped with an antibody–antigen based recognition element. Abstract : We evaluate the application of surfactant-free liquid-phase exfoliated MoS2 nanosheets as a nanoplatform for a cancer detection and treatment system equipped with an antibody–antigen based recognition element. Employing antigen–antibody binding, we increased the probability of the endocytosis of MoS2 nanosheets into CAIX expressing cells by 30%. The nanosheets are functionalized with a specific antibody M75, which forms an antigen–antibody complex with CAIX. The bioconjugation of MoS2 nanosheets involves biocompatible components with low cytotoxicity, verified in the tested cell lines by fluorescence-based cell viability assay. The cellular internalization is quantified by flow cytometry, while the internalization is confirmed by label-free confocal Raman imaging. Raman measurements show increased lysosomal activity in the proximity of the internalized nanoplatforms.